Measuring Customer-Oriented Organizational Citizenship Behavior on the Employees of Railway Transportation Service Provider - Dhevy Puswiartika; Zahrotur Rusyda Hinduan; Marina Sulastiana; Diana Harding (Binus Business Review, 2019)
This research aimed to describe Customer-Oriented Organizational Citizenship Behavior (CO-OCB) on the employees of the railway transportation service provider in Jakarta, Indonesia. A survey research was conducted by distributing the questionnaires to the employees and conducting a Focus Group Discussion (FGD). The sampling was taken by using a convenience sampling technique. The participants were 161 employees from different job levels. Consisting of managers, supervisors, and staff. Data analysis, the researchers used descriptive statistics analysis and inferential analysis with the Kruskal Wallis test by using Statistical Package for the Social Sciences software for Windows 21.0 and theme analysis. The results show that generally, the respondents have high COOCB. Then, the result of the inferential analysis shows that there are significant differences among CO-OCB. The dominant dimension shown by the employees is organizational compliance, followed by other dimensions such as sportsmanship, helping behavior, self-development, civic virtue, individual initiative, and organizational loyalty. The results also suggest that CO-OCB on the employees is influenced by individual characteristic factors like working attitude, and contextual factors.